Specifying Process Views for a Measurement, Evaluation, and Improvement Strategy. (19th February 2012) - Becker Becker, Pablo Pablo; Lew Lew, Philip Philip; Olsina Olsina, Luis Luis
Abstract : Any organization that develops software strives to improve the quality of its products. To do this first requires an understanding of the quality of the current product version. Then, by iteratively making changes, the software can be improved with subsequent versions. But this must be done in a systematic and methodical way, and, for this purpose, we have developed a specific strategy called SIQinU ( Strategy for understanding and Improving Quality in Use ). SIQinU recognizes problems of quality in use through evaluation of a real system-in-use situation and proposes product improvements by understanding and making changes to the product's attributes. Then, reevaluating quality in use of the new version, improvement gains can be gauged along with the changes that led to those improvements. SIQinU aligns with GOCAME ( Goal-Oriented Context-Aware Measurement and Evaluation ), a multipurpose generic strategy previously developed for measurement and evaluation, which utilizes a conceptual framework (with ontological base), a process, and methods and tools. Since defining SIQinU relies on numerous phase and activity definitions, in this paper, we model different process views, for example, taking into account activities, interdependencies, artifacts, and roles, while illustrating them with excerpts from a real-case study.